Penambahan madu dalam pengenceran sperma terhadap motilitas spermatozoa, fertilisasi dan daya tetas telur ikan Patin Siam, Pangasius hipophthalmus - Marthin, Lutfi; Watung, Juliaan Ch.; Kalesaran, Ockstan J.; Ginting, Elvi L.; Sinjal, Hengky J.; Salindeho, Indra R.N. (Universitas Sam Ratulangi, 2018)
This research aimed to determine the optimal doses of honey addition on the sperm dilution to optimize spermatozoa motility, fertilization and hatchability of Patin Siam eggs (Pangasius hypophthalmus). The experimental design used was Complete Random Design (RAL). Diluent solution consisted of a physiological NaCl 0.9% and honey. Treatment doses of honey in aqueous diluent sperm tested as treatments were A (0 mL), B (0.2 mL), C (0.4 mL) and D (0.6 mL), each with three replications. Observations made included spermatozoa motility, fertilization and eggs hatchability. The research results showed that the addition of honey had a significant influence on motility, fertilization, and eggs hatchability. This study concluded that the addition of honey in sperm diluent solution with a dose of 0.6 mL of honey in 99.4 mL of NaCl could increase the spermatozoa motility and fertilization of Patin siam. Keywords: honey, motility, fertilization, hatchability, Pangasius hipophthalmus